Physical activity in prevention of Alzheimer’s disease (literature review) - K. A. Mashkovich; V. N. Grigorieva (Лечащий Врач, 2021)
The article is focused on the current scientific evidence of the role of daily physical activity and special motor training in Alzheimer’s disease prevention as well as in slowing-down of cognitive decline in the already developed disease.